Health risk behaviours among people with severe mental ill health during the COVID-19 pandemic: Analysis of linked cohort data. - Emily Peckham; Victoria Allgar; Suzanne Crosland; Paul Heron; Gordon Johnston; Elizabeth Newbronner; Panagiotis Spanakis; Ruth Wadman; Lauren Walker; Simon Gilbody (PLoS ONE)
Background People with severe mental ill health (SMI) experience a mortality gap of 15-20 years. COVID-19 has amplified population health inequalities, and there is concern that people with SMI will be disproportionately affected. Understanding how health risk behaviours have changed during the pandemic is important when developing strategies to mitigate future increases in health inequalities. Methods We sampled from an existing cohort of people with SMI. Researchers contacted participants by phone or post to invite them to take part in a survey about how the pandemic had affected them. We asked people about their health risk behaviours and how these had changed during the pandemic. We created an index of changed behaviours, comprising dietary factors, smoking, lack of exercise, and drinking patterns. By creating data linkages, we compared their responses during pandemic restrictions to responses they gave prior to the pandemic. Outcomes 367 people provided health risk data. The mean age of the participants was 50.5 (range = 20 to 86, SD ± 15.69) with 51.0% male and 77.4% white British. 47.5% of participants reported taking less physical activity during the pandemic and of those who smoke 54.5% reported smoking more heavily. Self-reported deterioration in physical health was significantly associated with an increase in health risk behaviours (adjusted OR for physical health 1.59, 95%CI 1.22-2.07; adjusted OR for Age 0.99, 95%CI 0.98-1.00). Interpretation COVID-19 is likely to amplify health inequalities for people with SMI. Health services should target health risk behaviours for people with SMI to mitigate the immediate and long lasting impacts of the COVID-19 pandemic.